Abraham Lincoln : Lawyer, leader, legend - Fontes, Justine (DK readers, 2009)
This book follows the life story of Abraham Lincoln, from his boyhood on the frontier, to his election as president, to his leadership during the Civil War. Along the way, readers will learn important facts about slavery, politics, and other aspects of American history.